The Level of Social Intelligence and its Relationship with professional Competencies of School Principals in Jordan: - - Al-Baher, Ibrahim; Shawabkeh, Jwan (Technium Social Sciences Journal, 2024)
The current study aimed to reveal the level of social intelligence among school principals in Bani Kinana District in Jordan, and its relationship to the level of their professional competencies. The researcher used the descriptive analytical method, where the study sample consisted of (98) individuals. To achieve the objectives of the study a "questionnaire" was prepared and used to collect its data after verifying its validity and reliability, and using the SPSS program to analyze its data. The results of the study showed: The level of social intelligence among the principals of public schools in the Bani Kenana District, from their viewpoint was at medium level. And the level of professional competencies came at medium level. There is a positive, statistically significant correlation at the level (α ≤ 0.05) between the average estimates of the sample members on the social intelligence level scale and their estimates on the professional competency scale. There are no statistically significant differences at the level (α ≤ 0.05) between the average estimates of the sample members on all areas of the level of social intelligence & professional competencies among the principals of public schools in the Bani Kenana District according to the different study variables (gender, educational qualification, years of administrative experience). In light of the results, the study came out with several recommendations, including: - Number of training courses and programs for the development and activation of social intelligence among school principals. - Work to develop the professional competencies of school principals so that they can perform their duties and work tasks with distinction and mastery, which is positively reflected on the outputs that achieve the desired and desired goals of the educational process.